2023
DOI: 10.1590/0100-29452023042
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of chincuya seeds (Annona purpurea Moc. &Sessé ex Dunal) and embryonic growth under dry warm storage

Abstract: In Mexico, Annona purpurea Moc. &Sessé ex Dunal, chincuya is found in mountains and family gardens. It is used as food (fruits), traditional medicine (leaves, stems, roots, seeds, bark), wood in construction, papermaking, carpentry, rope making, and as fuel. There is not enough information on the seed, nor on germination management, which is scarce, prolonged and erratic. Considering that the morphophysiological dormancy is the probable cause, it was necessary, within a broader project, to start with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…A sudden drop in viability occurred on the twelfth month of storage (Figure 2). Vidal-Lezama et al noted that embryos grew during warm-dry storage until the sixth month [8], coinciding with the viability data observed here. Similarly, González-Esquinca et al found that A. macroprophyllata seed viability did not change throughout the 8-month storage evaluation [11].…”
Section: Viabilitysupporting
confidence: 90%
See 3 more Smart Citations
“…A sudden drop in viability occurred on the twelfth month of storage (Figure 2). Vidal-Lezama et al noted that embryos grew during warm-dry storage until the sixth month [8], coinciding with the viability data observed here. Similarly, González-Esquinca et al found that A. macroprophyllata seed viability did not change throughout the 8-month storage evaluation [11].…”
Section: Viabilitysupporting
confidence: 90%
“…Other mechanisms that might explain the after-ripening effect include non-enzymatic reactions that eliminate germination inhibitors, reactive oxygen species, and antioxidants [36], membrane alterations [37], and specific protein degradation through the proteasome [38]. Taiz and Zeiger mention that developing seeds synthesize gibberellins [19], and following the results found by Vidal-Lezama et al, who pointed out that chincuya embryos grow during warm-dry storage [8], it is possible to assume a continuum in the synthesis of gibberellins (although not exclusively) in the seed. On the other hand, the location of the species in the phylogenetic tree and its relationship with dormancy should be noted.…”
Section: Germinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest viability corresponded to months 6 and 9, although without statistical significance, except in the twelfth month where viability suddenly decreased. However, [29] it was pointed out that with the same storage, embryos grew until the sixth month. Similarly, [11] found that the A. macroprophyllata seed viability does not change throughout the 8-month storage evaluation.…”
Section: Viabilitymentioning
confidence: 99%